INTRASEASONAL VARIABILITY OF GUANO STAINS IN A REMOTELY SENSED PENGUIN COLONY USING UAV AND SATELLITE - M. Firla; O. Mustafa; C. Pfeifer; M. Senf; S. Hese (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2019)
Remote sensing of penguins gives a unique opportunity to observe ecosystem changes in the Antarctic and the Southern Ocean at a continent-wide scale. The extent of guano is the best proxy to the size of penguin populations but frequent cloud cover limits the number of available images. This study focuses on the correlation between guano coverage visible in aerial and satellite images and breeding pair numbers in the course of the breeding seasons 2016/17 and 2017/18 in a colony of Pygocelid penguins on Ardley Island (South Shetland Islands, Antarctica). Multitemporal UAV (Unmanned Aerial Vehicle) orthomosaics and high-resolution satellite images were collected of Ardley Island as well as data on breeding phenology, weather conditions and snow coverage. “Fresh” guano stains were classified using different methods of Geographical Object-based Image Analysis (GEOBIA) and differentiated from weathered guano stains. Analysis of this data shows that guano stains in an Antarctic Pygoscelid penguin colony undergo significant intraseasonal changes in extent, texture and spectral signature. Hence, the timing of image acquisition and the advance of snow melt during Antarctic spring matter when determining penguin populations and should be considered during the analysis. Our results show changes of up to 25 % of the total guano covered surface due to individual weather events and changes up to 80 % in the time between the peak of egg laying and the occurrence of the first crèche.